Faktor-Faktor yang Mempengaruhi E-Loyalty Kepada Konsumen E-Commerce di Kota Batam - Angeline, Angeline; Setyawan, Agustinus (Jurnal Ilmiah Poli Bisnis, 2022)
In this day and age, many people use E-Commerce for shopping. The purpose of this research is to examine the effect of the independent variables, namely E-Service Quality, E-Trust, Perceived Value, Security/Privacy and Website Design on the dependent variable, namely E-Loyalty through mediation of E-Satisfaction on e-commerce in Batam City. I also hope that this research can provide benefits for entrepreneurs who open businesses on the E-Commerce platform so that their business runs smoothly and increases sales. In addition to providing benefits for entrepreneurs who already have a business on this E-Commerce platform, of course, it can also provide benefits for people who want to open a business, both online and offline. The sample of this research includes 5 e-commerce companies, namely Shopee, Tokopedia, Lazada, Bukalapak and Blibli. The population used is people who live in the city of Batam who use or have shopped on E-Commerce sites. The number of samples required is 350 respondents. In the data analysis of this study, researchers used SPSS to test respondent data and Smart PLS to test the results of answers that had been generated from questionnaires to residents in Batam City which were distributed via g-form. Keywords : E-Commerce, E-Satisfaction, E-Loyalty